THE STANDARD OF LIVING OF HOUSEHOLDS IN POLAND COMPARED TO OTHER EU MEMBER STATES (JOURNAL OF ADVANCES IN AGRICULTURE, 2015)
The objective of this article is to present the standard of living of households in Poland in comparison with other EU member states. The starting point for analysis was the economic condition of Poland against the background of other EU member states. The next step consisted of assessment of the standard of living of inhabitants of individual EU member states on the basis of financial condition of households and the structure of consumption expenditure. It was found that the differences within the EU in terms of economic development and the standard of living of households still remain substantial.